CNN BASED PATHWAY CONTROL TO PREVENT COVID SPREAD USING FACE MASK AND BODY TEMPERATURE DETECTION (Journal of Pharmaceutical Negative Results, 2022)
Airborne diseases cause detriment in the human life. Many were found in history such as TB, SARS, MERS andrecently COVID 19. These diseases hit the dead rate and crushes health and wealth of the world population. Mostly,airborne diseases will spread rapidly in crowdy places. Especially, in case of COVID-19, Wearing mask andmonitoring body temperature by individual is good solution to prevent rapid spread of the disease. So, keeping safetymeasures in monitoring face mask and body temperature is crucial in crowdy places such as Airports, railway stations,Bus Stations, malls, temples, etc. is obligatory. With a focus on emphasizing the health of the people we proposedintegrated system that monitors body temperature and face mask of each individual and open/close pathway gate toallow after knee verification. Proposed Prototype uses Raspberry pi to monitor Face mask using CNN and Arduino tomonitor body temperature and enable motor drivers to open or close the pathway Gate. Efficiency and loss of ProposedCNN model was trained and tested with multiple epoches.